2004
DOI: 10.1038/nsmb845
|View full text |Cite
|
Sign up to set email alerts
|

Centromeric chromatin exhibits a histone modification pattern that is distinct from both euchromatin and heterochromatin

Abstract: Post-translational histone modifications regulate epigenetic switching between different chromatin states. Distinct histone modifications, such as acetylation, methylation and phosphorylation, define different functional chromatin domains, and often do so in a combinatorial fashion. The centromere is a unique chromosomal locus that mediates multiple segregation functions, including kinetochore formation, spindle-mediated movements, sister cohesion and a mitotic checkpoint. Centromeric (CEN) chromatin is embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
590
7
5

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 518 publications
(627 citation statements)
references
References 37 publications
25
590
7
5
Order By: Relevance
“…Classically, centromeres were assumed to be composed of heterochromatin. However, the groundbreaking study of Sullivan and Karpen revealed that the kinetochorespecific histone CENP-A resides in a specialized chromatin environment, which has been termed 'centrochromatin' (Sullivan and Karpen, 2004). A more recent study has shown that centrochromatin has a histone modification pattern resembling that found in the downstream body of transcribed genes (Bergmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classically, centromeres were assumed to be composed of heterochromatin. However, the groundbreaking study of Sullivan and Karpen revealed that the kinetochorespecific histone CENP-A resides in a specialized chromatin environment, which has been termed 'centrochromatin' (Sullivan and Karpen, 2004). A more recent study has shown that centrochromatin has a histone modification pattern resembling that found in the downstream body of transcribed genes (Bergmann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Besides CENP-A, active centromeres display a specific profile of post-translational modifications on their associated histone H3-containing nucleosomes (Bergmann et al, 2011;Lam et al, 2006;Ribeiro et al, 2010;Sullivan and Karpen, 2004). This special chromatin, which has been termedx 'centrochromatin' (Sullivan and Karpen, 2004), suggests a functional link between the local chromatin environment and kinetochore function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, although H3K4 methylation was considered a mark of euchromatin, it is present at heterochromatic centromeric DNA in fission yeast, Drosophila, and human cells (Sullivan and Karpen 2004;Cam et al 2005). Diminished levels of H3K4 methylation affects the recruitment and deposition of the histone CENPA at centromeres of human artificial chromosomes, providing direct evidence for the involvement of Set1-mediated methylation in kinetochore function (Bergmann et al 2011).…”
Section: Set1 Complex Function Is Required With Nima For Normal Transmentioning
confidence: 99%
“…In fact, the kinetochore protein Hec1 (A. nidulans Ndc80) is phosphorylated by the human NIMA-related kinase, Nek2, thereby contributing to proper chromosome segregation (Chen et al 2002;Wei et al 2011). In addition, it is possible that deficiencies in Set1-mediated modulation of Aurora target phosphorylation (Zhang et al 2005) also contributes to the genetic interactions with NIMA.Importantly, although H3K4 methylation was considered a mark of euchromatin, it is present at heterochromatic centromeric DNA in fission yeast, Drosophila, and human cells (Sullivan and Karpen 2004;Cam et al 2005). Diminished levels of H3K4 methylation affects the recruitment and deposition of the histone CENPA at centromeres of human artificial chromosomes, providing direct evidence for the involvement of Set1-mediated methylation in kinetochore function (Bergmann et al 2011).…”
mentioning
confidence: 99%